Financial Performance of Healthcare Firms: The Case of Korea - Park, Jun Woo; Guahk, Seyoung (International Journal of Economics and Financial Issues, 2017)
The purpose of this study is to analyze the financial performance and financial characteristics of healthcare companies. Healthcare firms are statistically significantly higher than non-healthcare companies in terms of several ratios such as research and development (R and D) cost ratio, selling general and administrative expenses ratio, Tobin’s Q, return on equity, return on sales, total capital growth and sales growth. The cost of sales ratio is statistically lower than that of non-healthcare companies, which implies that healthcare companies spend much R and D costs for technological innovation, and as a result, they increase corporate value by lowering the cost of sales ratio and improving profitability. The profitability, growth, and leverage of healthcare companies were found to influence more on corporate value for the healthcare firms than those of non-healthcare companies. This result can be interpreted as reflecting the expectation that future cash flow will be more influenced by profitability, growth, and leverage of healthcare companies. Keywords: Healthcare, Healthcare Firms, Financial Performance JEL Classifications: I11, I32